2013
DOI: 10.1016/j.jcdr.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Putative antioxidant property of sesame oil in an oxidative stress model of myocardial injury

Abstract: a b s t r a c tBackground: Sesame oil is a potent antioxidant dietary source for human health. Oxidative stress through generation of free radicals damages the myocardium in different experimental condition. The present research was designed to evaluate the antioxidant property of chronic oral administration of sesame oil against isoproterenol induced myocardial injury. Methods and results: Male Wistar albino rats were randomly divided into five groups (n ¼ 6) and treated as per treatment protocol with two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Hemodynamic indexes, myocardial enzymes and myocardial infarct size all reflect the degree of I/R damage. Previous studies have demonstrated that the primary mechanisms underlying MIRI may include excessive production of free radicals, infiltration of inflammatory cells, mitochondrial dysfunction and apoptosis of myocardial cells (19,(23)(24)(25). Therefore, reducing the generation of free radicals (26), inhibiting the inflammatory response and suppressing apoptosis (27) may markedly reduce I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic indexes, myocardial enzymes and myocardial infarct size all reflect the degree of I/R damage. Previous studies have demonstrated that the primary mechanisms underlying MIRI may include excessive production of free radicals, infiltration of inflammatory cells, mitochondrial dysfunction and apoptosis of myocardial cells (19,(23)(24)(25). Therefore, reducing the generation of free radicals (26), inhibiting the inflammatory response and suppressing apoptosis (27) may markedly reduce I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Sesame oil is a strong antioxidant dietary source for human 11 . Previous studies have shown that sesame oil has improving effects on memory and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu & Liu, reported that the level of lipid peroxidation, hydroxyl radical, and nitrite levels reduced, whereas the antioxidant enzyme SOD and CAT increased in SO‐treated LPS‐induced oxidative stress rat models (Hsu, Chiang et al, ). In addition, parenterally SO‐treated animal groups showed attenuation of hepatic disorder, although the symptoms were different when the SO was given orally (Ahmad et al, ; Hsu & Liu, ; Saleem, Chetty, & Kavimani, ). However, superoxide anion decreased and GSH increased in the oral SO groups (Ahmad et al, ; Saleem et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, parenterally SO‐treated animal groups showed attenuation of hepatic disorder, although the symptoms were different when the SO was given orally (Ahmad et al, ; Hsu & Liu, ; Saleem, Chetty, & Kavimani, ). However, superoxide anion decreased and GSH increased in the oral SO groups (Ahmad et al, ; Saleem et al, ). Ahmad et al () showing that dietary SO behaves as an antioxidant, resulting in increased enzymatic and nonenzymatic antioxidants activity in the middle cerebral artery occlusion (MCAO rat model against MCAO‐induced cerebral ischemia injury (Ahmad et al, ).…”
Section: Resultsmentioning
confidence: 99%